Peran Artificial Intelligence dalam Meningkatkan Kualitas Layanan dan Kepuasan Pelanggan pada Bisnis E-Commerce Sebuah Systematic Literature Review - Ferry Febrian; Sandy Firdaus; Sahra Waldi (SPT. haria Journal and Education Center Publishing, 2026)
The rapid integration of Artificial Intelligence (AI) into E-Commerce platforms has fundamentally transformed how businesses deliver services and engage with customers. This Systematic Literature Review examines the role of AI in enhancing Service Quality and Customer Satisfaction within the E-Commerce sector. Following the PRISMA 2020 guidelines, this study systematically searched five major academic databases Scopus, Web of Science, ScienceDirect, IEEE Xplore, and Google Scholar for peer-reviewed articles published between 2020 and 2025. A total of 82 articles met the inclusion criteria and were subjected to thematic analysis and narrative synthesis. The findings reveal that AI technologies, including chatbots, personalized recommendation systems, virtual assistants, and predictive analytics, significantly contribute to improved Service Quality across multiple dimensions responsiveness, reliability, personalization, and efficiency. AI-powered Service Quality has been shown to enhance customer experience (β = 0.770, p < 0.001), perceived usefulness, and problem-solving ability, which subsequently strengthen expectation confirmation and Customer Satisfaction. However, the literature also identifies critical challenges, including privacy concerns, algorithmic bias, the digital divide, and consumer aversion to AI in certain contexts. The study proposes an integrated conceptual framework linking AI service attributes to Customer Satisfaction outcomes and identifies several research gaps, including the lack of longitudinal studies, limited examination of generative AI applications, underexplored cultural moderators, and insufficient attention to ethical AI implementation. This review contributes to the theoretical understanding of AI-Service Quality-Customer Satisfaction relationships and offers practical implications for E-Commerce practitioners, policymakers, and future researchers.